Optimum Design of Box Structure of High Power Mine Reducer - Jiguo Wang; Junyuan Li; JunyYunan Chen (Jixie chuandong)
In view of the market demand for high-power mine reducer, taking the innovative design of 2 000 kW mine reducer as the research object. The monitoring system and water cooling system of reducer are introduced. The model of the box is reconstructed with 3D design software UG. The strength analysis of its innovative structure is carried out by using finite element analysis software. A reference for the design of domestic high-power reducer in the future is provided.